Optimizing service management and digital sales in MSMES with sales information system - Frans Sudirjo; Rahmat Rahmat; Kraugusteeliana Kraugusteeliana; Susi Indriyani; Abdurrahman Sadikin (Jurnal Mantik, 2023)
Through digitization and sales information systems, MSMEs can improve their efficiency, market reach, and consumer experience in a digital era that is becoming increasingly advanced. The urgency of the research emphasizes on the rising level of business competition, urging MSMEs to adapt rapidly. If micro, small, and medium-sized enterprises (MSMEs) cannot keep up with technological trends and continue to rely on conventional methods, they risk losing market share and consumer loyalty. MSMEs can also be hindered by inefficient management and inability to utilize information technology. The research aims to implement a sales information system for MSMEs in optimizing service and sales management using the System Development Life Cycle (SDLC) method. According to the findings of the study, there are eight features of the sales information system that are tailored to the analysis of functional requirements in business processes in MSMEs, and the results of blackbox testing indicate that the system features have run successfully